Exploring the Rural Tourism Perception of Local People and Farmers: The Case Study of Mordogan in İzmir, Turkey: Rural Tourism Perception of Local People and Farmers (Cuadernos de Desarrollo Rural, 2022)
This study aimed to examine rural tourism perception of local people and farmers living in Mordoğan, Izmir, Turkey.  Main material of this study was obtained from survey conducted with 103 local people and 65 farmers.  In this study, factor analysis was used to determine rural tourism perceptions of local people and farmers. According to the analysis result, six main factors related to rural tourism perceptions of local people and farmers which can be measured by 19 statements were determined. These factors were named as economic, socio-cultural, environmental, interaction, awareness and local development factors. Cronbach alpha coefficient of factors was calculated as 0.840 and it explained 73.29 % of total variance. The economic factor was found the most important explanatory factor.